Expression of oil palm (Elaeis guineensis) polyisoprenoids in response to Ganoderma boninense infection - DADANG AFANDI; MOHAMMAD BASYUNI; LOLLIE AGUSTINA P. PUTRI; DIANA CHALIL; INDRA SYAHPUTRA (Society for Indonesian Biodiversity, 2019)
Afandi D, Basyuni M, Putri LAP, Chalil D, Syahputra I. 2019. Expression of oil palm (Elaeis guineensis) polyisoprenoids in response to Ganoderma boninense infection. Biodiversitas 20: 68-76. Currently, oil palm is an important economic crop and has become one of the world's major vegetable oils as well as a potential source of biodiesel. Unfortunately, oil palm plantations in Asia, particularly in Indonesia and Malaysia face the threat of basal stem root diseases caused by Ganoderma sp. Various methods and approaches have been made to select the oil palm that is tolerant to Ganoderma boninense, among others using biochemical selection. This research aimed to analyze polyisoprenoids expressionof oil palm tolerant to G. boninense using two-dimensional thin layer chromatography (2D-TLC). The plant material used in this trial weretwo cross-series of genetic materials belonging to PT Socfindo, that were known to have certain levelsof tolerance to G. boninense. The first wasa cross-series of 15-year-old oil palm in the field, and the secondwasa new cross-series for an early detection in the nursery stage. The results showed that there werediversitiesin the expression of polyisoprenoids between tissues, treatments, and level of tolerance. Polyprenols with a chain length of C45-C65 and dolichols of C45-C55were detected in the leaf tissue but not found in the root tissue. Polyprenols with a carbon chain length of C80-C100 occurred in infected palm root tissue but did not in the healthy oil palm. The increase of polyisoprenoid (polyprenol and dolichol) in infected and inoculated root tissues it is presumablydue to the plant biochemical response to the presence of G. boninense attack. Cluster analysis demonstrated distinct groups of polyisoprenoid carbon-chains betweenroot and leaf tissues of oil palm mature and seedling. Interestingly, in the absence of G. boninense infection, the polyisoprenoid carbon chain pattern in the tolerant oil palm seedlingroot tissue is different from that in the susceptible seedlings. Thus, the polyisoprenoid carbon chain pattern can be considered as a potential biochemical marker for the screening of oil palm tolerance to G. boninense.